Effects of Cationic Polypeptide on CaCO3 Crystallization and Sand Solidification by Microbial-Induced Carbonate Precipitation - Nawarathna, T.H.K.; Nakashima, K.; Fujita, M.; Takatsu, M.; Kawasaki, S. (ACS Publications, 2018)
The use of organic additives to improve microbial-induced carbonate precipitation (MICP) is a novel and innovative idea. This study is the first to address the effects of the cationic biopolymer poly-lysine (poly-Lys) on CaCO3 crystallization and sand solidification by MICP. CaCO3 was precipitated with and without poly-Lys by hydrolysis of urea by using ureolytic bacteria, Pararhodobacter sp., in the presence of CaCl2 under different experimental conditions. The morphologies and polymorphs of the oven-dried precipitates were investigated using scanning electron microscopy and X-ray diffraction. A larger amount of precipitate was obtained with poly-Lys than with the conventional MICP method. The curve for the relationship between the poly-Lys concentration and amount of precipitate was bell shaped. In the presence of poly-Lys, the morphology changed from rhombohedral crystals to twin spherical crystals. The effects of poly-Lys on sand solidification were also investigated by syringe solidification at different bacterial injection intervals with and without poly-Lys. The addition of poly-Lys gave strongly cemented sand specimens that were stronger than those obtained by the conventional method. The results confirm that poly-Lys addition is an effective and sustainable way to improve the MICP efficiency and production of green materials for engineering applications.
Keywords: Biocement; Biomineral; Calcium carbonate; Morphology; Polylysine